Preparation method of lithium metal negative electrode with double-layer structure

By adopting a double-layer structure design in the lithium metal anode material of lithium ion batteries, the potential difference between the hollow carbon tube and the copper current collector wrapped in nitrogen-containing carbon materials is used to uniformly deposit lithium metal, which solves the problem of lithium metal anode material in The problems caused by side reactions and "dead lithium" improve the circulation performance and safety of the battery.

CN119480934AInactive Publication Date: 2025-02-18SHENZHEN QINGYAN HAOLONG NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411671771.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The side reaction between the lithium metal anode material of existing lithium-ion batteries and the formation of "dead lithium" between the lithium anode and the electrolyte, resulting in low utilization rate of active lithium and short battery cycle life, and poses safety risks.

Method used

The lithium metal negative electrode preparation method adopts a double-layer structure. By loading a hollow carbon tube wrapped with nitrogen-containing carbon material on the copper current collector, the lithium metal is uniformly deposited by the potential difference between the two carbon layers to form a lithium metal negative electrode material with a sandwich structure. .

Benefits of technology

Through the design of the double-layer structure, the uniform deposition of lithium metal and the stability of the electrode interface are improved, the time when lithium dendrites come into contact with the separator is extended, and the circulation performance and safety of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480934A_ABST
    Figure CN119480934A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium metal negative electrode with a double-layer structure, and belongs to the field of battery materials. The preparation method of the lithium metal negative electrode with the double-layer structure comprises the following steps: loading a central control carbon tube uniformly wrapped by a nitrogen-containing carbon material on a copper current collector to prepare a lithium metal negative electrode material; the obtained negative electrode material and a lithium sheet form a pair of batteries, charge and discharge tests are carried out, and a lithium layer can be uniformly deposited between the nitrogen-containing carbon material and a hollow carbon tube; 0.5 g of catkin is adopted, and deionized water is added for cleaning three times; the cleaned catkins are put into a 150m HNO3 solution, stirring is performed, suction filtration is performed after stirring, and then three times of water washing are performed. Cyanuric chloride is adopted as a nitrogen-containing carbon material precursor, pyrrole type nitrogen and pyridine type nitrogen can be generated after high-temperature carbonization of cyanuric chloride, and the atoms have lithium affinity and can be used as carriers when lithium metal is embedded, so that the nitrogen-containing carbon material can be used for preparing a nitrogen-containing carbon material; and the lithium metal can be better immersed into the middle layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a method for preparing a double-layer lithium metal negative electrode. Background Art

[0002] Sufficient energy is one of the important conditions to support the sustainable development of society. With the depletion of traditional fossil energy and the increasingly serious environmental damage it brings, the development of new clean energy and the realization of efficient energy storage and conversion have become urgent needs of human society. Chemical energy, as an efficient and convenient energy storage and conversion device, has played an important role in the progress of human civilization. The development history of chemical energy has exceeded 200 years. There are many forms of batteries such as lead-acid batteries, nickel-cadmium batteries, nickel-hydrogen batteries, zinc-manganese batteries, and lithium-ion batteries. Among them, lithium-ion batteries have the advantages of high average output voltage, low self-discharge, no memory effect, and long service life. They are widely used in various fields of human life. However, with the rapid development of social intelligence, energy storage grids, electric transportation, miniaturized and high-energy-consuming portable electronic devices and other fields have put forward higher requirements for the energy density of energy storage devices. However, limited by the theoretical specific capacity of graphite materials (372mAh / g), lithium-ion batteries with carbon materials such as graphite as negative electrodes are gradually approaching the theoretical limit of their energy density. Therefore, it is urgent to develop negative electrode materials with higher energy density.

[0003] Among the existing negative electrode materials, lithium metal is considered to be the most promising high-energy negative electrode material. 2( NCM) positive electrode, the theoretical capacity density of the battery can be as high as about 1000Wh / Kg. Although lithium metal batteries have significant advantages in energy density compared with current lithium-ion batteries, they also have serious problems, such as side reactions between the lithium negative electrode and the electrolyte and the formation of "dead lithium". The problem of low utilization of active lithium and short battery cycle life. The potential safety hazards caused by the growth of lithium dendrites, these problems seriously hinder the practical application of lithium metal batteries. Therefore, achieving uniform deposition of lithium and stabilization of the electrode interface is of great significance to promoting the development of high-energy lithium metal batteries. We provide a method for preparing a double-layer lithium metal negative electrode. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a double-layer lithium metal negative electrode in response to the above technical problems. The method has the advantages of two carbon layers with different potentials loaded on a copper current collector. When a half-point cell is formed with a lithium sheet for charge and discharge testing, the lithium metal will use the potential difference between the two carbon layers to penetrate into the middle layer, providing a spatial structure for the generation of dendrites, thereby improving the cycle performance of the battery.

[0005] To achieve this purpose, the present invention provides a method for preparing a double-layer lithium metal negative electrode, which adopts the following technical embodiments:

[0006] A method for preparing a double-layer lithium metal negative electrode material, the method for preparing a lithium metal negative electrode material comprising the following steps:

[0007] S1: A copper current collector is loaded with a carbon tube uniformly wrapped with nitrogen-containing carbon material to prepare a lithium metal negative electrode material;

[0008] S2: The obtained negative electrode material and lithium sheet are combined into a battery for charge and discharge test. The lithium layer can be evenly deposited between the nitrogen-containing carbon material and the hollow carbon tube.

[0009] Furthermore, the preparation method of the hollow carbon tube comprises the following steps:

[0010] S3: Use 0.5 g catkins and wash three times with deionized water;

[0011] S4: Put the cleaned catkins into 150m HNO3 solution, stir, filter after stirring, and then wash with water three times;

[0012] S5: Then put it into a drying oven for drying to obtain catkin flakes, i.e. hollow carbon tube precursors.

[0013] Furthermore, the method for preparing the hollow carbon tube wrapped with nitrogen-containing carbon material comprises the following steps:

[0014] S6: Soak the catkins in 15 ml of 0.5 mol / L cyanuric chloride solution for 12 h, and then dry them in a drying oven at 60° C. for 12 h to obtain a nitrogen-containing carbon material-wrapped hollow carbon tube precursor material;

[0015] S7: placing the precursor material into a high temperature tube furnace, raising the temperature to 600°C at a rate of 5°C / min, keeping the temperature for 5 hours, and then cooling the furnace to room temperature to obtain a hollow carbon tube precursor material wrapped with a nitrogen-containing carbon material.

[0016] Furthermore, the preparation method of the above-mentioned composite lithium metal negative electrode material comprises the following steps:

[0017] S8: The nitrogen-containing carbon material wrapped hollow carbon tube and the binder are mixed in a ratio of 7-9 parts: 3-1 parts, N-methyl-2-pyrrolidone is used as a solvent, and after mixing evenly, a slurry is made and coated on a copper foil, and a base material is obtained after vacuum drying.

[0018] Furthermore, the base material obtained in the above step S8 and the lithium sheet form a counter electrode.

[0019] Furthermore, the content of cyanuric chloride in the solution in step S6 is 5 to 80 ml, and the mass fraction is 0.2 mol to 5 mol.

[0020] Furthermore, in the above step S7, the carbonized product is placed in a high temperature tube furnace for carbonization, the carbonization temperature is 500-1000° C., and the carbonization time is 2 h to 8 h.

[0021] Furthermore, the substrate material obtained in the above step S8 is applied to lithium metal batteries.

[0022] Furthermore, in the above step S4, the concentration of the HNO3 solution is 0.5 mol / L, and the stirring time is 20 min.

[0023] Furthermore, in the above step S5, the catkins are placed in a drying oven at a drying temperature of 80° C. for a drying time of 12 hours.

[0024] The present invention has at least the following beneficial effects:

[0025] In the present invention, a precursor material of a hollow carbon tube wrapped with a nitrogen-containing carbon material is prepared by a simple immersion method, and then a hollow carbon tube material wrapped with a nitrogen-containing carbon material is prepared by a high-temperature carbonization method, and then coated on a copper foil to obtain a lithium metal negative electrode material with a sandwich structure;

[0026] In the present invention, cyanuric chloride is used as a nitrogen-containing carbon material precursor. After high-temperature carbonization, cyanuric chloride will produce pyrrolic nitrogen and pyridinic nitrogen. These atoms have lithium affinity and can be used as carriers when lithium metal is embedded, so that lithium metal can be better immersed in the middle layer.

[0027] In the present invention, low-cost catkins are used as a precursor for preparing hollow carbon tubes. After high-temperature carbonization, catkins will form hollow carbon tubes with a three-dimensional structural network and will form N and O heteroatoms. These heteroatoms are also lithium-philic and help lithium metal to be more evenly deposited on the hollow carbon tubes.

[0028] In the present invention, cyanuric chloride is combined with catkins, and the hollow carbon tube material wrapped by the nitrogen-containing carbon material formed after high-temperature carbonization has two lithium-philic nitrogen atoms, which can make lithium metal deposit evenly. In addition, the two carbon layers have a potential difference. When the copper-lithium composite belt is used as a counter electrode for testing, the lithium metal will utilize the lithium-philic atoms and the potential difference to be evenly deposited between the two carbon layers, thereby extending the contact time between the lithium dendrites and the diaphragm and improving the cycle life.

[0029] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a comparison diagram of full cycle charging and capacity testing of Example 1 of the present invention and NMC and NCA batteries;

[0031] Figure 2 This is a comparison diagram of full cycle charging and capacity testing of Example 1 and Example 2 of the present invention;

[0032] Figure 3 This is a comparison diagram of full cycle charging and capacity testing of Embodiment 1, Embodiment 2 and Embodiment 3 of the present invention;

[0033] Figure 4 This is a comparison diagram of full cycle charging and capacity testing of Embodiment 1, Embodiment 2, Embodiment 3 and Embodiment 4 of the present invention;

[0034] Figure 5 It is a comparative relationship diagram of full cycle charging and capacity testing of Example 1, Example 2, Example 3, Example 4 and Example 5 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical embodiments and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0036] The application principle of the present invention is described in detail below in conjunction with the accompanying drawings.

[0037] A method for preparing a double-layer lithium metal negative electrode material, the method for preparing a lithium metal negative electrode material comprising the following steps:

[0038] S1: A copper current collector is loaded with a carbon tube uniformly wrapped with nitrogen-containing carbon material to prepare a lithium metal negative electrode material;

[0039] S2: The obtained negative electrode material and lithium sheet are combined into a battery for charge and discharge test. The lithium layer can be evenly deposited between the nitrogen-containing carbon material and the hollow carbon tube.

[0040] A precursor material of hollow carbon tubes wrapped with nitrogen-containing carbon material is prepared by a simple immersion method, and then a hollow carbon tube material wrapped with nitrogen-containing carbon material is prepared by a high-temperature carbonization method, which is then coated on copper foil to obtain a lithium metal negative electrode material with a sandwich structure.

[0041] The method for preparing the hollow carbon tube comprises the following steps:

[0042] S3: Use 0.5 g catkins and wash three times with deionized water;

[0043] S4: Put the cleaned catkins into 150m HNO3 solution, stir, filter after stirring, and then wash with water three times;

[0044] S5: Then put it into a drying oven for drying to obtain willow catkins, i.e., hollow carbon tube precursors. Low-cost willow catkins are used as the precursor for the preparation of hollow carbon tubes. After high-temperature carbonization, the catkins will form hollow carbon tubes with a three-dimensional structural network and will form N, O heteroatoms. These heteroatoms are also lithium-philic, which helps to deposit lithium metal more evenly on the hollow carbon tubes.

[0045] The method for preparing hollow carbon tubes wrapped with nitrogen-containing carbon material comprises the following steps:

[0046] S6: Soak the catkins in 15 ml, 0.5 mol / L cyanuric chloride solution for 12 h, and then dry them in a drying oven at 60 ° C for 12 h to obtain a nitrogen-containing carbon material wrapped hollow carbon tube precursor material. Cyanuric chloride is used as a nitrogen-containing carbon material precursor. Cyanuric chloride will produce pyrrolic nitrogen and pyridinic nitrogen after high-temperature carbonization. These atoms are lithium-philic and can be used as carriers when lithium metal is embedded, so that lithium metal can be better immersed in the middle layer;

[0047] S7: placing the precursor material into a high temperature tube furnace, raising the temperature to 600°C at a rate of 5°C / min, keeping the temperature for 5 hours, and then cooling the furnace to room temperature to obtain a hollow carbon tube precursor material wrapped with a nitrogen-containing carbon material.

[0048] The preparation method of the composite lithium metal negative electrode material comprises the following steps:

[0049] S8: The nitrogen-containing carbon material wrapped hollow carbon tube and the binder are mixed in a ratio of 7-9 parts: 3-1 parts, N-methyl-2-pyrrolidone is used as a solvent, and after mixing evenly, a slurry is made and coated on a copper foil, and a base material is obtained after vacuum drying.

[0050] The base material obtained in step S8 and the lithium sheet form a counter electrode.

[0051] Among them, the content of the cyanuric chloride solution in step S6 is 5 to 80 ml, and the mass fraction is 0.2 mol to 5 mol. Cyanuric chloride is combined with catkins. The hollow carbon tube material wrapped by the nitrogen-containing carbon material formed after high-temperature carbonization has two lithium-philic nitrogen atoms, which can make the lithium metal deposited evenly. In addition, the two carbon layers have a potential difference. When the copper-lithium composite belt is used as the counter electrode for testing, the lithium metal will use the lithium-philic atoms and the potential difference to be evenly deposited between the two carbon layers, thereby extending the contact time between the lithium dendrites and the diaphragm and improving the cycle life.

[0052] Wherein, in step S7, the carbonized product is placed in a high-temperature tube furnace for carbonization, the carbonization temperature is 500-1000° C., and the carbonization time is 2 h to 8 h.

[0053] The base material obtained in step S8 is applied to lithium metal batteries.

[0054] Wherein, in step S4, the concentration of the HNO3 solution is 0.5 mol / L, and the stirring time is 20 min.

[0055] Wherein, in step S5, the catkins are placed in a drying oven, the drying temperature is 80° C., and the drying time is 12 hours.

[0056] Example 1

[0057] The preparation method of the composite lithium metal negative electrode material of this embodiment is as follows:

[0058] (1) Preparation of hollow carbon tube precursor: Take 0.5g catkins, add deionized water to rinse three times, put the washed catkins into 150ml, 0.5mol / L HNO3 solution, stir for 20min, filter, and then wash three times. Put the washed catkins into a drying oven and dry them at 80℃ for 12h to obtain catkins, i.e. hollow carbon tube precursor;

[0059] (2) Preparation of nitrogen-containing carbon material-wrapped hollow carbon tube precursor: soak the catkins in 15 ml, 1.5 mol / L cyanuric chloride solution for 12 h and then dry to obtain a nitrogen-containing carbon material-wrapped hollow carbon tube precursor;

[0060] (3) Place the nitrogen-containing carbon material wrapped hollow carbon tube precursor material into a high-temperature tube furnace at 5°C

[0061] / min to 650°C, and then cooled to room temperature with the furnace after keeping the temperature for 4h. After taking out, the carbonized material was ground with an agate mortar for 30min to obtain a nitrogen-containing carbon material-wrapped hollow carbon tube composite material;

[0062] (4) mixing the prepared nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material with a binder in a ratio of 7:2, using N-methyl-2-pyrrolidone as a solvent, mixing evenly, grinding for 40 minutes, making a slurry, coating it on a copper foil, and vacuum drying to obtain a nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material;

[0063] (5) The nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material was cut into a disc with a diameter of 12 mm as the working electrode, and a lithium sheet was used as the counter electrode and a ceramic diaphragm, and a lithium metal electrolyte was assembled into a 2025 button cell.

[0064] The battery was tested for cycle performance, and the specific capacity was 30 mAh / cm 2 .

[0065] The battery was subjected to gram capacity and cycle tests at a test temperature of 25°C and a test voltage range of 2.8 to 4.4V. Example 1, the NMC battery and the NCA battery were connected to a charging cabinet, first charged to 4.4V with a 0.1C constant current, then charged to full charge at a constant voltage, and the gram capacity data was recorded. After standing for 5 minutes, the battery was charged to 4.4V with a 0.2C constant current, then charged at a constant voltage, and discharged at 0.5C after standing for 5 minutes until the cycle capacity retention rate of the cycled battery was less than 80%. The battery cycle test was completed. The test results are as follows: Figure 1 shown.

[0066] Example 2

[0067] The preparation method of the composite lithium metal negative electrode material of this embodiment is as follows:

[0068] (1) Preparation of hollow carbon tube precursor: Take 0.5g catkins, add deionized water to rinse three times, put the washed catkins into 150ml, 0.5mol / L HNO3 solution, stir for 20min, filter, and then wash three times. Put the washed catkins into a drying oven and dry at 80℃ for 12h to obtain catkins flakes, i.e. hollow carbon tube precursor;

[0069] (2) Preparation of nitrogen-containing carbon material-wrapped hollow carbon tube precursor: soak willow catkins in 15 ml, 0.5 mol / L cyanuric chloride solution for 12 h and then dry to obtain a nitrogen-containing carbon material-wrapped hollow carbon tube precursor;

[0070] (3) placing the nitrogen-containing carbon material wrapped hollow carbon tube precursor material into a high-temperature tube furnace, raising the temperature to 650°C at a rate of 5°C / min, keeping the temperature for 4 hours, and then cooling it to room temperature with the furnace. After taking it out, grinding the carbonized material with an agate mortar for 30 minutes to obtain a nitrogen-containing carbon material wrapped hollow carbon tube composite material;

[0071] (4) mixing the prepared nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material with a binder in a ratio of 7:2, using N-methyl-2-pyrrolidone as a solvent, mixing evenly, grinding for 40 minutes, making a slurry, coating it on a copper foil, and vacuum drying to obtain a nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material;

[0072] (5) The nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material was cut into a disc with a diameter of 12 mm as the working electrode, and a lithium sheet was used as the counter electrode and assembled with a ceramic diaphragm and a lithium metal electrolyte to form a 2025 button cell.

[0073] The battery was tested for cycle performance, and the specific capacity was 30 mAh / cm 2 .

[0074] The battery was subjected to gram capacity and cycle tests at a test temperature of 25°C and a test voltage range of 2.8 to 4.4V. Example 1 and Example 2 were connected to a charging cabinet, first charged to 4.4V with a 0.1C constant current, then charged to full charge at a constant voltage, and the gram capacity data was recorded. After standing for 5 minutes, the battery was charged to 4.4V with a 0.2C constant current, then charged at a constant voltage, and discharged at 0.5C after standing for 5 minutes until the cycle capacity retention rate of the cycled battery was less than 80%. The battery cycle test was completed. The test results are shown as follows: Figure 2 shown.

[0075] Example 3

[0076] The preparation method of the composite lithium metal negative electrode material of this embodiment is as follows:

[0077] (1) Preparation of hollow carbon tube precursor: Take 0.5g catkins, add deionized water to rinse three times, put the washed catkins into 150ml, 0.5mol / L HNO3 solution, stir for 20min, filter, and then wash three times. Put the washed catkins into a drying oven and dry at 80℃ for 12h to obtain catkins flakes, i.e. hollow carbon tube precursor;

[0078] (2) Preparation of nitrogen-containing carbon material-wrapped hollow carbon tube precursor: soak the catkins in 15 ml, 1 mol / L cyanuric chloride solution for 12 h and then dry to obtain a nitrogen-containing carbon material-wrapped hollow carbon tube precursor;

[0079] (3) placing the nitrogen-containing carbon material wrapped hollow carbon tube precursor material into a high-temperature tube furnace, raising the temperature to 650°C at a rate of 5°C / min, keeping the temperature for 4 hours, and then cooling it to room temperature with the furnace. After taking it out, grinding the carbonized material with an agate mortar for 30 minutes to obtain a nitrogen-containing carbon material wrapped hollow carbon tube composite material;

[0080] (4) mixing the prepared nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material with a binder in a ratio of 7:2, using N-methyl-2-pyrrolidone as a solvent, mixing evenly, grinding for 40 minutes, making a slurry, coating it on a copper foil, and vacuum drying to obtain a nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material;

[0081] (5) The nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material was cut into a disc with a diameter of 12 mm as the working electrode, and a lithium sheet was used as the counter electrode and assembled with a ceramic diaphragm and a lithium metal electrolyte to form a 2025 button cell.

[0082] The battery was tested for cycle performance, and the specific capacity was 30 mAh / cm 2 .

[0083] The battery was subjected to gram capacity and cycle tests at a test temperature of 25°C and a test voltage range of 2.8 to 4.4V. Example 1, Example 2 and Example 3 were connected to a charging cabinet, first charged to 4.4V with a 0.1C constant current, then charged to full charge at a constant voltage, and the gram capacity data was recorded. After standing for 5 minutes, the battery was charged to 4.4V with a 0.2C constant current, then charged at a constant voltage, and discharged at 0.5C after standing for 5 minutes until the cycle capacity retention rate of the cycled battery was less than 80%. The battery cycle test was completed. The test results are as follows: Figure 3 shown.

[0084] Example 4

[0085] The preparation method of the composite lithium metal negative electrode material of this embodiment is as follows:

[0086] (1) Preparation of hollow carbon tube precursor: Take 0.5g catkins, add deionized water to rinse three times, put the washed catkins into 150ml, 0.5mol / L HNO3 solution, stir for 20min, filter, and then wash three times. Put the washed catkins into a drying oven and dry at 80℃ for 12h to obtain catkins flakes, i.e. hollow carbon tube precursor;

[0087] (2) Preparation method of hollow carbon tube precursor material wrapped with nitrogen-containing carbon material: soak willow catkins in 15 ml, 2 mol / L cyanuric chloride solution for 12 hours and then dry to obtain hollow carbon tube precursor material wrapped with nitrogen-containing carbon material;

[0088] (3) placing the nitrogen-containing carbon material wrapped hollow carbon tube precursor material into a high-temperature tube furnace, raising the temperature to 650°C at a rate of 5°C / min, keeping the temperature for 4 hours, and then cooling it to room temperature with the furnace. After taking it out, grinding the carbonized material with an agate mortar for 30 minutes to obtain a nitrogen-containing carbon material wrapped hollow carbon tube composite material;

[0089] (4) mixing the prepared nitrogen-containing carbon material wrapped hollow carbon tube composite material with a binder in a ratio of 7:2, using N-methyl-2-pyrrolidone as a solvent, mixing evenly, grinding for 40 minutes, making a slurry, coating it on a copper foil, and vacuum drying to obtain a nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material;

[0090] (5) The nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material was cut into a disc with a diameter of 12 mm as the working electrode, and a lithium sheet was used as the counter electrode and assembled with a ceramic diaphragm and a lithium metal electrolyte into a 2025 button cell.

[0091] The battery was tested for cycle performance, and the specific capacity was 30 mAh / cm 2 .

[0092] The battery was subjected to gram capacity and cycle tests at a test temperature of 25°C and a test voltage range of 2.8 to 4.4V. Example 1, Example 2, Example 3 and Example 4 were connected to a charging cabinet, first charged to 4.4V with a 0.1C constant current, then charged to full charge at a constant voltage, and the gram capacity data was recorded. After standing for 5 minutes, the battery was charged to 4.4V with a 0.2C constant current, then charged at a constant voltage, and discharged at 0.5C after standing for 5 minutes until the cycle capacity retention rate of the cycled battery was less than 80%. The battery cycle test was completed. The test results are as follows: Figure 4 shown.

[0093] Example 5

[0094] The preparation method of the composite lithium metal negative electrode material of this embodiment is as follows:

[0095] (1) Preparation of hollow carbon tube precursor: Take 0.5g catkins, add deionized water to rinse three times, put the washed catkins into 150ml, 0.5mol / L HNO3 solution, stir for 20min, filter, and then wash three times. Put the washed catkins into a drying oven and dry at 80℃ for 12h to obtain catkins flakes, i.e. hollow carbon tube precursor;

[0096] (2) Preparation method of hollow carbon tube precursor material wrapped with nitrogen-containing carbon material: soak willow catkins in 15 ml, 2.5 mol / L cyanuric chloride solution for 12 hours and then dry to obtain hollow carbon tube precursor material wrapped with nitrogen-containing carbon material;

[0097] (3) placing the nitrogen-containing carbon material wrapped hollow carbon tube precursor material into a high-temperature tube furnace, raising the temperature to 600°C at a rate of 5°C / min, keeping the temperature for 4 hours, and then cooling it to room temperature with the furnace. After taking it out, grinding the carbonized material with an agate mortar for 30 minutes to obtain a nitrogen-containing carbon material wrapped hollow carbon tube composite material;

[0098] (4) mixing the prepared nitrogen-containing carbon material wrapped hollow carbon tube composite material with a binder in a ratio of 7:2, using N-methyl-2-pyrrolidone as a solvent, mixing evenly, grinding for 40 minutes, making a slurry, coating it on a copper foil, and vacuum drying to obtain a nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material;

[0099] (5) The nitrogen-containing carbon material wrapped hollow carbon tube composite substrate material was cut into a 12 mm diameter disc as the working electrode, and a lithium sheet was used as the counter electrode, and assembled with a ceramic diaphragm and a lithium metal electrolyte into a 2025 button cell.

[0100] The battery was tested for cycle performance, and the specific capacity was 30 mAh / cm 2 .

[0101] The battery was subjected to gram capacity and cycle tests at a test temperature of 25°C and a test voltage range of 2.8 to 4.4V. Example 1, Example 2, Example 3, Example 4 and Example 5 were connected to a charging cabinet, first charged to 4.4V with a 0.1C constant current, then charged to full charge at a constant voltage, and the gram capacity data was recorded. After standing for 5 minutes, the battery was charged to 4.4V with a 0.2C constant current, then charged at a constant voltage, and discharged at 0.5C after standing for 5 minutes until the cycle capacity retention rate of the cycled battery was less than 80%. The battery cycle test was completed. The test results are as follows: Figure 5 shown.

[0102] The battery was subjected to gram capacity and cycle tests at a test temperature of 25°C and a test voltage range of 2.8 to 4.4V. Examples 1-5 were connected to a charging cabinet and first charged to 4.4V with a 0.1C constant current and then charged to full charge with a constant voltage. The gram capacity data was recorded. After standing for 5 minutes, the battery was charged to 4.4V with a 0.2C constant current and then charged at a constant voltage. After standing for 5 minutes, the battery was discharged with 0.5C until the cycle capacity retention rate of the cycled battery was less than 80% to complete the battery cycle test.

[0103] Table 1. The gram capacity of the lithium metal negative electrode material in the embodiment on the half electrode of the lithium sheet

[0104] Example Gram capacity (mAh / g) Example 1 182 Example 2 178 Example 3 180 Example 4 176 Example 5 178

[0105] Table 1 shows the gram capacity of the lithium metal negative electrode material for the half-electrode of the lithium sheet and the battery cycle performance in the embodiment. It can be seen that for the nitrogen-containing carbon material wrapped hollow carbon tube as the lithium metal negative electrode base material, its gram capacity and cycle performance are better than those of other embodiments. For different concentrations of cyanuric chloride, its properties are different. When the concentration is 1.5 mol / L, its cycle performance is significantly better than that of other groups. This is because cyanuric chloride contains nitrogen-carbon material, and its nitrogen atom is pyrrole-type nitrogen. This type of nitrogen atom has lithium affinity, which can make lithium metal climb to the middle layer structure better and deposit in the middle layer better. Excessive or insufficient cyanuric chloride concentration will cause pyrrole-type nitrogen to block or not be enough as a carrier for lithium metal to climb to the middle layer structure, so that lithium cannot be deposited in the middle layer structure, which affects the cycle performance of the battery; and the carbonization temperature also has a great influence on it. Too low temperature will lead to incomplete carbonization, which will affect the conductivity of the battery. Too high temperature will also cause carbon atoms to adhere, thereby affecting the conductivity of the battery.

[0106] The above embodiments are only used to illustrate rather than limit the technical embodiments of the present invention. Relevant technical personnel in the field may make reasonable modifications or equivalent substitutions to the present invention, but any modifications and partial substitutions that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

[0107] The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A method for preparing a double-layer lithium metal negative electrode, characterized in that: The method for preparing the lithium metal negative electrode material comprises the following steps: S1: A carbon nanotube uniformly wrapped with nitrogen-containing carbon material is loaded on a copper current collector to prepare a lithium metal negative electrode material; S2: The obtained negative electrode material and lithium sheet are combined into a battery for charge and discharge test. The lithium layer can be evenly deposited between the nitrogen-containing carbon material and the hollow carbon tube.

2. The method for preparing a double-layer lithium metal negative electrode according to claim 1, characterized in that: The method for preparing the hollow carbon tube comprises the following steps: S3: Use 0.5 g of catkins and wash them three times with deionized water; S4: Put the cleaned catkins into 150m HNO3 solution, stir, filter after stirring, and then wash with water three times; S5: Then put it into a drying oven for drying to obtain catkin flakes, i.e. hollow carbon tube precursors.

3. The method for preparing a double-layer lithium metal negative electrode according to claim 1, characterized in that: The method for preparing the hollow carbon tube wrapped with nitrogen-containing carbon material comprises the following steps: S6: Soak the catkins in 15 ml of 0.5 mol / L cyanuric chloride solution for 12 h, and then dry them in a drying oven at 60° C. for 12 h to obtain a nitrogen-containing carbon material-wrapped hollow carbon tube precursor material; S7: placing the precursor material into a high temperature tube furnace, raising the temperature to 600°C at a rate of 5°C / min, keeping the temperature for 5 hours, and then cooling the furnace to room temperature to obtain a hollow carbon tube precursor material wrapped with a nitrogen-containing carbon material.

4. The method for preparing a double-layer lithium metal negative electrode according to claim 1, characterized in that: The preparation method of the above-mentioned composite lithium metal negative electrode material comprises the following steps: S8: The nitrogen-containing carbon material wrapped hollow carbon tube and the binder are mixed in a ratio of 7-9 parts: 3-1 parts, N-methyl-2-pyrrolidone is used as a solvent, the slurry is mixed evenly and coated on a copper foil, and the base material is obtained after vacuum drying.

5. The method for preparing a double-layer lithium metal negative electrode according to claim 4, characterized in that: The base material obtained in the above step S8 and the lithium sheet form a counter electrode.

6. The method for preparing a double-layer lithium metal negative electrode according to claim 3, characterized in that: The content of cyanuric chloride in the solution in step S6 is 5 to 80 ml, and the mass fraction is 0.2 mol to 5 mol.

7. The method for preparing a double-layer lithium metal negative electrode according to claim 3, characterized in that: In the above step S7, the carbonized product is placed in a high temperature tube furnace for carbonization at a temperature of 500-1000° C. for a carbonization time of 2 h to 8 h.

8. The method for preparing a double-layer lithium metal negative electrode according to claim 4, characterized in that: The base material obtained in the above step S8 is applied to lithium metal batteries.

9. The method for preparing a double-layer lithium metal negative electrode according to claim 2, characterized in that: In the above step S4, the concentration of the HNO3 solution is 0.5 mol / L, and the stirring time is 20 min.

10. The method for preparing a double-layer lithium metal negative electrode according to claim 2, characterized in that: In the above step S5, the catkins are placed in a drying oven at a drying temperature of 80° C. for a drying time of 12 hours.

Citation Information

Patent Citations

  • Composite lithium metal negative pole and preparation method thereof

    CN110660968A

  • Composite current collector for eliminating thermal runaway risk hidden danger of battery pack and preparation method of composite current collector

    CN116885111A

  • Biochar material, preparation method thereof and application of biochar material in lithium metal secondary battery

    CN117566738A